Isopods in the Bioremediation of Invasive Seaweeds? First Experience with the Seaweed Rugulopteryx okamurae Mass Dumped on Beaches - Daniel Patón; José Carlos García-Gómez (Journal of Marine Science and Engineering)
Since 2015, the invasive seaweed Rugulopteryx okamurae has triggered the most serious marine macrophyte invasion in Europe. Its huge coastal biomass dumped on beaches generates health problems, strong odors, impacts on tourism, and high clean-up costs, but it also constitutes a new potential marine resource that offers significant prospects for exploitation. In this sense, as a circular economy strategy, seaweed bioremediation with isopods (Isopoda, Crustacea, Arthropoda) was experimented on for the first time. Specimens of Porcellio laevis (native terrestrial isopod) were obtained from urban parks and kept in terrariums with adequate humidity and temperature control. A sample of 150 adult specimens was divided into six batches of 25 animals. Three batches were fed with 100 g of mulch of Quercus pyrenaica leaves (control) and three with a diet composed of 100 g of mulch of algae (treatment). P. laevis consumed up to 1.5 times their weight per day on the algae diet, with little or no weight loss and adequate reproduction rates. The weight of the isopods averaged 1.6 g in the seaweed group and 2.5 g in the control group. However, high mortality was observed in both mancas and adults in the treatment group. In this sense, the average number of mancas per cm2 was 0 in the algae group and 325 in the control group. Despite this, the results are promising, and consequently, we propose to encourage research with isopods due to their high voracity, high prolificacy, and resistance to invasive algal recycling. Future work should explore what percentage of R. okamurae prevents diterpene mortality of isopods and other invertebrates. This is a preliminary step towards the massive bioremediation of spring and summer blooms of R. okamurae. This work contributes to highlighting this abundant marine resource.